Clintonite-bearing assemblages in chondrodite marbles from the contact aureole of the Trebicsky Pluton, Moldanubian Zone, Bohemian Massif - Houzar,S.; Novak,M. (Journal of the Czech Geological Society, 2006)
Clintonite is a minor to accessory mineral in chondrodite marbles. They represent a rare type of metacarbonate rocks in the Varied Unit of the Moldanubian Zone, forming thin bodies enclosed in migmatites. Clintonite occurs exclusively in marbles from contact aureole of melanocratic ultrapotassic granites (durbachites) of the Trebic Pluton. Chondrodite marbles consist of dominant calcite, less abundant dolomite; amounts of silicates vary from &#126 5 to 30 vol. %. The early mineral assemblage Dol+Cal+Prg±Phl is replaced by the assemblage Chn+Cli+Cal ±Chl I ±Spl. Accessory minerals include fluorapatite, diopside, tremolite, pyrrhotite, and rare zircon and baddeleyite. Violet fluorite occurs on late fissures. Clintonite forms colourless to pale green flakes and sheaf-like aggregates, up to 2 mm in size. It has extraordinary high Si (2.739-2.986 apfu) and Si/Al ratio (0.52-0.60). The contents of Fetot (0.041-0.128 apfu), Na (0.035-0.134 apfu), Ti (0.004-0.024 apfu) and K (≤ 0.005 apfu) are low. High concentrations of F (0.437-1.022 apfu) corresponding up to 26 % of the F-component are the highest ever-recorded in clintonite. Mineral reactions producing clintonite, which is closely associated with more abundant chondrodite (XF = 0.45-0.67), are not clear in detail, because textural relations often do not show any apparent replacement features. The simplified reactions involving diopside, pargasite and/or phlogopite: (5) Dol + Phl + Di + H2O = Cli + Chn + Chl I + Cal + CO2 + K2O, (6,7) Dol + Prg (and/or Phl) = Cli + Chn + Cal + CO2 + K2O ± Na2O, and (8) Dol + Phl (and/or Prg) + SiO2aq + F = Cli + Chn + Spl + Cal + CO2 + K2O ± Na2O seem the most probable. Retrograde chlorite II formed by the reaction: (9) Chn + Cli + CO2 = Chl + Cal. Mineral assemblages of clintonite-bearing chondrodite marbles are product of regional-scale contact ("periplutonic") LP metamorphism at: P &#126 2-4 kbar; T &#126 620-730 °C. The reactions might be buffered internally, if pargasite and/or phlogopite were a source of F and Al; however, high modal content of chondrodite in most samples is likely related to influx of H2O, Si and F from an external source. It is also supported by isotopic composition of calcite (δ13Ccalcite = -0.6 &#150 -4.2 ‰ PDB; δ18Ocalcite = 12.5-15.7 ‰ SMOW). Fluorine-rich fluids very likely stabilized the assemblage chondrodite + clintonite relative to compositionally equivalent assemblages involving Mg-silicate (forsterite and/or clinohumite) + chlorite (and/or spinel) + calcite.
Keywords: Clintonite; chemical composition; fluorine; chondrodite marble; Moldanubian Zone; Bohemian Massif